Hsp70 Genotypes and Heat Tolerance of Commercial and Native Chickens Reared in Hot and Humid Conditions - M Duangjinda (Brazilian Journal of Poultry Science)
ABSTRACT Heat tolerance in poultry production was obtained attention due to the need for genetic lines that can withstand climate changes. This study aimed at investigating heat tolerance in commercial and native broiler genetics, as well as the physiological and growth performance responses of HSP70 genotypes submitted to heat stress. In Experiment I, heterophil:lymphocyte (H:L) ratio, as an indicator of heat tolerance, was compared between commercial broilers (n = 100) and Thai native chickens (n = 100). Growing chickens (with similar initial weight) of each genetic strain were randomly divided into two groups: 1) thermoneutral environment (26 oC ± 2 oC) and 2) heat stress (36 oC ± 2 oC). The results showed that native chickens originating from a tropical environment presented lower H:L ratio and mortality rate compared with commercial broilers. In Experiment II, HSP70 genotypes were compared. PCR-RFLP was applied to identify the genotypes (C1C1, n = 38; C1C2, n = 38; and C2C2, n = 28). Ten-week-old chickens of each genotype were evaluated in the same environments described in Experiment I. Heat-stress indicators - respiratory rate (RR), cloacal temperature (CT), packed cell volume (PCV), and average daily gain (ADG) - were measured for three weeks. The significant difference in PCV indicated that C2C2 chickens were less tolerant to heat stress compared to other genotypes. The RR, CT, and ADG were not significantly different among all genotypes. Since the C2C2 genotype was shown to be sensitive to heat stress, C1C1 and C1C2 could be used as markers for heat-tolerant genetic strains of Thai indigenous chickens and hybrid commercial lines.